The impact of crash simulation on productivity and problem-solving in automotive R&D - Philipp Spethmann; Stefan H. Thomke; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
This paper analyzes the impact of the virtual tool 'crash simulation' on automotive R&D over the last 35 years. The research carried out in this context identifies and investigates distinct phases respectively stages of the potential of crash simulations based on the Finite Element Method and the stages' impact on automotive R&D in-depth. In a study of German Original Equipment Manufacturers' (OEM) utilization of crash simulations, the evolution of this tool is explored and its impact on productivity and problem-solving investigated. We draw upon literature about crash simulations in car development projects, the utilization of crash simulations in related tasks, and recent literature about the overall impact of crash simulations on automotive R&D. The significance of the tool 'crash simulation' for the OEMs is emphasized by means of corresponding landmark projects. Our study is based on qualitative research based on 29 in-depth interviews with experts from all of the major German OEMs and experts from the US-American academia. Our analysis results in partitioning the tool's evolution into five phases. Each phase is characterized by its impact on automotive R&D. The phases induced profound changes either in productivity or in the ability of problem-solving. Understanding these profound changes and its triggers holds the key to better understanding the potential of virtual simulation tools and the requirements necessary to unlock this potential.
Keywords: 650